Answer :




Using the splitting middle term - the middle term of the general equation is divided in two such values that:


Product = a.c


For the given equation a = 2; b = - 5; c = 2


= 2.2 = 4


And either of their sum or difference = b


= - 5


Thus the two terms are - 4 and - 1


Difference = - 4 - 1 = - 5


Product = - 4. - 1 = 4




2x(x-2)-1(x-2) = 0


(2x-1)(x-2) = 0


(2x-1) = 0 or (x-2) = 0



Hence the roots of equation are


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses